2016
DOI: 10.1007/s11207-016-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

The Revised Sunspot Record in Comparison to Cosmogenic Radionuclide-Based Solar Activity Reconstructions

Abstract: Recent revisions in the sunspot records illustrate the challenges related to obtaining a 400-year-long observational record of past solar-activity changes. Cosmogenic radionuclides offer the possibility of obtaining an alternative and completely independent record of solar variability. Here, we illustrate that these records offer great potential for quantitative solar-activity reconstructions far back into the past, and we provide updated radionuclide-based solar-activity reconstructions for the past 2000 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 70 publications
4
76
0
5
Order By: Relevance
“…Differences between the 14 C-and 10 Be-based reconstructions manifest themselves mainly in the phasing and differences in secular trends, for example in the duration and timing of the LMM. The SATIRE-based solar activity reconstruction is also in good overall agreement with a solar activity reconstruction that is exclusively based on cosmic ray measurement/proxy data via a combination of 14 C and neutron monitor data (Muscheler et al, 2016).…”
Section: Solar Variationssupporting
confidence: 63%
See 1 more Smart Citation
“…Differences between the 14 C-and 10 Be-based reconstructions manifest themselves mainly in the phasing and differences in secular trends, for example in the duration and timing of the LMM. The SATIRE-based solar activity reconstruction is also in good overall agreement with a solar activity reconstruction that is exclusively based on cosmic ray measurement/proxy data via a combination of 14 C and neutron monitor data (Muscheler et al, 2016).…”
Section: Solar Variationssupporting
confidence: 63%
“…Clette et al, 2014;Usoskin et al, 2016a;Lockwood et al, 2016). The agreement with the exclusively cosmic ray-based reconstruction (Muscheler et al, 2016;Usoskin et al, 2014Usoskin et al, , 2016b indicates that this approach does not introduce major discontinuities in the solar forcing record.…”
Section: A3 Volcanic Forcingsupporting
confidence: 56%
“…However, this method can be hardly applied for the 20th century because of the anthropogenic effects (fossil fuel burning, land-use changes and atmospheric nuclear bomb tests) and climate changes that affect the cosmogenic isotope transport and deposition. As a result, applications of the cosmogenic isotope data to assess quality of different SN reconstructions were also inconclusive and contradictory; Muscheler et al (2016) found, using an ad hoc normalization, that the high SN series agree with the cosmogenic record, but they did not analyse other sunspot series; Usoskin et al (2015) concluded that while low SN series agree with the cosmogenic 14 C data, the high series do not; Owens et al (2016b) suggested that all SN series agree more or less with cosmogenic 10 Be data, within the uncertainties. Probably, such ambiguity of the results is related to the fact that changes in the solar activity are governed by the 11-yr cycle that is, of course, synchronous in all the SN reconstructions, with the only difference being in the amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…forced cosmogenic radionuclide production signal via a curve fitting method enables the quasi-continuous synchronization of natural environmental archives (Adolphi and Muscheler, 2016;Muscheler et al, 2014).…”
mentioning
confidence: 99%
“…For example, Adolphi and Muscheler (2016) synchronized the Greenland ice core and IntCal13 time-scales for the last 11000 years. Synchronizing 10 Be records from varved lake sediments opens the opportunity for the synchronization of terrestrial paleoclimate records around the globe.…”
mentioning
confidence: 99%